2013
DOI: 10.1152/ajpgi.00130.2012
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous nuclear ribonucleoprotein A2/B1 is a tissue-specific aldosterone target gene with prominent induction in the rat distal colon

Abstract: The steroid hormone aldosterone enhances transepithelial Na(+) reabsorption in tight epithelia and is crucial to achieve extracellular volume homeostasis and control of blood pressure. One of the main transport pathways regulated by aldosterone involves the epithelial Na(+) channel (ENaC), which constitutes the rate-limiting step of Na(+) reabsorption in parts of the distal nephron and the collecting duct, the distal colon, and sweat and salivary glands. Although these epithelial tissues share the same recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Our findings confirm that Aldo leads to enhanced EGFR expression via interaction with the EFGR promoter, as previously shown by Grossmann et al (10) ANG II-inducing TGF-␤ and its downstream mediators resulting in matrix accumulation, inflammation, and apoptosis (24), and Aldo-inducing EGF, promoting myofibroblast and fibroblast growth and proliferation. Recently, a similar conclusion has been reached that Aldo stimulates ENaC expression in rat distal colon via the MR but not the glucocorticoid receptor whereas it stimulates an increase in SGK-1 via the glucocorticoid receptor (11).…”
Section: Discussionmentioning
confidence: 57%
“…Our findings confirm that Aldo leads to enhanced EGFR expression via interaction with the EFGR promoter, as previously shown by Grossmann et al (10) ANG II-inducing TGF-␤ and its downstream mediators resulting in matrix accumulation, inflammation, and apoptosis (24), and Aldo-inducing EGF, promoting myofibroblast and fibroblast growth and proliferation. Recently, a similar conclusion has been reached that Aldo stimulates ENaC expression in rat distal colon via the MR but not the glucocorticoid receptor whereas it stimulates an increase in SGK-1 via the glucocorticoid receptor (11).…”
Section: Discussionmentioning
confidence: 57%
“…The hnRNPs are mostly present in the nucleus; however, some hnRNPs, including hnRNP A2B1, seem to shuttle between the nucleus and cytoplasm ( 19 ). hnRNP A2B1 also regulates a variety of cellular pathways from cell cycle progression to tissue development in cancer cell lines ( 20 ). In this study, we found that hnRNP A2B1 regulated MAP kinase signaling in 38B9 cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These cells lack endogenous expression of MR or GR [57]. Cells were cultured and transfected as described before [57][58][59]. Briefly, cells were cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum at 37 • C in a 5% CO 2 atmosphere.…”
Section: Synthesis Of Dihydropiridinesmentioning
confidence: 99%